On the constitution of the no-world in torture (2014)
In his book Morality Self-knowledge and Human Suffering. An Essay on the Loss of Confidence in the World, Josep Corbí accomplishes an analysis of Jean Améry´s own description of the torture he was victim in 1943. The central aspects of this analysis are accounted by the terms “the loss of confidence in the world”. The purpose in this paper is to broaden the description of the characteristics of the loss produced by torture, in the sense alluded by Corbí, as well as in a further sense: the actual loss of the world. This kind of loss refers to the way physical harm confines the victim to a sort of hermetic imprisonment in what Hannah Arendt calls “the sphere of the private”.